An exploration of the effectiveness of in-person and online versions of the induced hypocrisy paradigm to reduce smartphone use among young drivers. (October 2021) - Gauld, Cassandra; Watson, Barry; Lewis, Ioni; White, Katherine M.; Pammer, Kristen
Highlights: Development and application of an online version of the induced hypocrisy paradigm. Paradigm effective as an intervention for smartphone use among young drivers. Online version more effective than in-person at eliciting cognitive dissonance. Intervention groups more effective at reducing intention and behaviour over time. Online version may form part of mass campaigns against smartphone use while driving. Abstract: Worldwide, smartphone use is a major contributing factor to road crash among young drivers. While young drivers may be aware of their heightened crash risk and the legal penalties associated with this behaviour, young drivers continue to engage with their smartphones. The development of novel interventions targeting this behaviour is therefore crucial. The current 2 × 2 between groups experimental study ( N  = 153, 107F, 43 M, 1 other) investigated the concept of cognitive dissonance in relation to smartphone use among young drivers aged 17–25 years ( M age  = 20.66 SD  = 2.26). Specifically, it applied the induced hypocrisy paradigm to this context. The induced hypocrisy paradigm elicits cognitive dissonance by asking participants to both advocate for the desired behaviour and identify their engagement in the undesired behaviour. Participants are then motivated to change their behaviour to reduce the feelings of dissonance. The current study investigated the efficacy of both the traditional in-person methodology with a new online methodology. Analyses (e.g., ANCOVA) found that the online conditions were more effective than the in-person groups at eliciting dissonance and that the intervention conditions were more effective in reducing both intention and change in behaviour (from pre- to post-intervention) than the control groups. The intervention groups were also more likely to take/request a flyer about driver distraction. While more research is needed to corroborate these findings, these initial results suggest that cognitive dissonance occurs when young drivers use their smartphones and that the induced hypocrisy paradigm may be an effective intervention. In particular, this study's findings suggest that an online version of the induced hypocrisy paradigm has merit and may form part of future cost-effective, mass interventions.